Structural modifications of berberine and their binding effects towards polymorphic deoxyribonucleic acid structures: A review - Fu, Lanlan; Mou, Jiajia; Deng, Yanru; Ren, Xiaoliang (Frontiers in Pharmacology, 2022)
Berberine (BBR) is a plant derived quaternary benzylisoquinoline alkaloid, which has been widely used in traditional medicines for a long term. It possesses broad pharmacological effects and is widely applied in clinical. In recent years, the anti-tumor effects of BBR have attracted more and more attention of the researchers. The canonical right-handed double-stranded helical deoxyribonucleic acid (B-DNA) and its polymorphs occur under various environmental conditions and are involved in a plethora of genetic instability-related diseases especially tumor. BBR showed differential binding effects towards various polymorphic DNA structures. But its poor lipophilicity and fast metabolism limited its clinical utility. Structural modification of BBR is an effective approach to improve its DNA binding activity and bioavailability in vivo. A large number of studies dedicated to improving the binding affinities of BBR towards different DNA structures have been carried out and achieved tremendous advancements. In this article, the main achievements of BBR derivatives in polymorphic DNA structures binding researches in recent twenty years were reviewed. The structural modification strategy of BBR, the DNA binding effects of its derivatives, and the structure activity relationship (SAR) analysis have also been discussed.